Utilização da semente, casca e vagem da Moringa oleifera Lam no processo de biossorção para remoção de Diuron® de águas contaminadas - Souza, Héllen Karoline Spricigo de (2016)
Diuron® is a herbicide considered potentially toxic and causing problems to human health and the environment and has been frequently detected in surface waters and groundwaters. Conventional water treatments are not effective for the removal of Diuron®, so if you are looking for alternative treatments that are low cost and efficient removal of this contaminant water. Adsorption is a process that arises as an alternative to this. Moringa oleifera Lam, as a coagulant agent, has been gaining prominence in water treatment. Its use as a biosorbent was still little studied, but brings good prospects for the adsorption of contaminants. Thus, this study aimed to evaluate the biosorption of Diuron® in pod, seed bark (which are considered waste from obtaining the seeds) and M. oleifera seed. The biosorbents were characterized by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR) which was performed before and after the adsorption, and textural characterization was performed also by determining the specific surface area (BET), the area of micropores (t method), volume and micropores diameter (HK) and volume and mesoporous diameter (BJH) of each of the biosorbents. The pH of zero charge (pHPZC) was also analyzed. Batch tests were conducted and evaluated the effects of parameters contact time, pH, agitation speed, dose and particle size of biosorbent the biosorption process. Possession of the parameters that significantly influenced on biosorption, the kinetic study was performed. Models of pseudo-first and pseudo-second order kinetic data were adjusted, and the model that best fit to the data for the three adsorbents was the pseudo-second order. Adsorption isotherms were obtained at three temperatures (25, 35 and 45° C) and analyzed using the models of Langmuir, Freundlich, Dubinin-Radushkevich and Temkin. The results indicated that the data of adsorption of Diuron® in the pods, bark and seed of M. oleifera were better represented by the Freundlich model. The enthalpy thermodynamic properties ((∆H), entropy ((∆S) and Gibbs free energy ((∆G) showed that the biosorption of Diuron® was spontaneous and viable for three adsorbents studied. The seed showed endothermic behavior, while the seed bark and the pod showed an exothermic behavior. Based on these results, it is believed that the Diuron® adsorption process by the parties of the fruit of M. oleifera occurs for physisorption and chemisorption. Due to good capacity of removal of Diuron® (50 to 74%) and low cost, it can be said that the seed, seed bark and pod of M. oleifera are biosorbents promising materials for disposal of contaminated waters Diuron®.